“LONTO LEOK” SEBAGAI PRAKSIS KATEKESE KONTEKSTUAL GEREJA LOKAL MANGGARAI - Harbur, Agustinus Manfred (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
Catechesis as faith educational process is always contextual because faith is essentially involved in the struggle of concrete life. Catechesis of Manggaraian local church must be contextual. A suitable approach for this contextual catehesis is the